2013
DOI: 10.1115/1.4007046
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Burst in Flexible Pipes

Abstract: Usually when a large internal fluid pressure acts on the inner walls of flexible pipes, the carcass layer is not loaded, as the first internal pressure resistance is given by the internal polymeric layer that transmits almost all the loading to the metallic pressure armor layer. The last one must be designed to ensure that the flexible pipe will not fail when loaded by a defined value of internal pressure. This paper presents three different numerical models and an analytical nonlinear model for determining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 3 publications
2
10
0
Order By: Relevance
“…(10)(11)(12) with Eq. (8), it is possible to obtained a system of linear equations defined in terms of deformations, ie:…”
Section: Analytical Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…(10)(11)(12) with Eq. (8), it is possible to obtained a system of linear equations defined in terms of deformations, ie:…”
Section: Analytical Modelsmentioning
confidence: 99%
“…Neto et al [9,10] proposed a linear analytical formulation, assuming that the pressure armor has a relationship D t > 10, where D and t represents the outer diameter and wall thickness respectively, behave exactly as a thin-walled cylinder. Therefore, the authors suggested that the hoop stress can be represented by:…”
Section: Analytical Modelsmentioning
confidence: 99%
See 3 more Smart Citations